PENGEMBANGAN OBJEK WISATA PULAU BELIBIS DI KELURAHAN KAMPUNG JAWA KECAMATAN TANJUNG HARAPAN KOTA SOLOK - Rery Novio; Rizqi Akbar Nofli (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to assess the potential and development strategy of Belibis Island tourist attraction in Kampung Jawa Village, Tanjung Harapan District, Solok City, using the SOAR (Strengths, Opportunities, Aspirations, Results) analysis approach. Belibis Island is a natural tourist attraction with the main attraction in the form of a lake, the beauty of the landscape, and the potential for outdoor recreation, but its management is considered not optimal. This research uses descriptive qualitative methods with data collection techniques through observation, documentation, and interviews with stakeholders such as managers, and the Tourism Office. The results showed that the strength of Belibis Island lies in its natural potential and community support. Development opportunities include nature-based tourism trends and digital promotion. Development aspirations are directed at making Belibis Island a sustainable leading tourist destination, with expected results in the form of increased visitor numbers and economic contributions to local communities. This research recommends development strategies through increasing tourist attractions, providing adequate amenity, and strengthening community participation in tourism management.